Forgotten classics: E.T. Grether's (1966) Marketing and Public Policy. (18th August 2014) - Savitt, Ronald
Abstract : Purpose: – The purpose of this article is to revisit a forgotten classic in the marketing literature to provide a historical review of ET Grether's 1966 book, Marketing and Public Policy . Design/methodology/approach: – The approach combines a literature review with historical reflection by placing Grether's work in historical context. Findings: – Marketing and Public Policy offered a framework for examining and evaluating marketing practices and public policy responses based on Grether's mastery of a number of disciplines and his extensive research into public policy issues. His ideas are relevant to today's world, especially in light of technological developments and shifts in our moral compass since the 1960s. Originality/value: – ET Grether was a two-time recipient of the American Marketing Association's Paul D. Converse Award, Editor of the Journal of Marketing, President of the American Marketing Association and author of more than 100 articles and books. This is the first attempt to review what is arguably one of his most important publications, Marketing and Public Policy.